2014
DOI: 10.1007/978-3-319-09665-0_10
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional HDL: From Structure-Function-Relationships to Biomarkers

Abstract: Reduced plasma levels of HDL-C are associated with an increased risk of CAD and myocardial infarction, as shown in various prospective population studies. However, recent clinical trials on lipidmodifying drugs that increase plasma levels of HDL-C have not shown significant clinical benefit. Notably, in some recent clinical studies, there is no clear association of higher HDL-C levels with a reduced risk of cardiovascular events observed in patients with existing CAD. These observations have prompted researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
1
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 181 publications
(216 reference statements)
1
51
1
6
Order By: Relevance
“…Indeed, both absolute levels and profiles of total PC-P + PE-P(20:4) and PC-P + PE-P(22:6) at D0 and at D180 in native LDL, HDL2, and HDL3 obtained by LC/MS closely resembled those quantitated as total plasmalogen by HPLC protects against the action of a wide spectrum of reactive oxygen species (ROS) and attenuates LDL oxidation in part by removal of seeding LOOH species (21,22,24,26,27,32,34,51). Central to HDL-mediated antioxidative activity is the direct reduction of LOOHs by methionine residues of apoAI and apoAII, with conversion to residuespecific methionine sulfoxides (apoAI + 16, apoAI + 32, and apoAII + 16) (21,(30)(31)(32).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Indeed, both absolute levels and profiles of total PC-P + PE-P(20:4) and PC-P + PE-P(22:6) at D0 and at D180 in native LDL, HDL2, and HDL3 obtained by LC/MS closely resembled those quantitated as total plasmalogen by HPLC protects against the action of a wide spectrum of reactive oxygen species (ROS) and attenuates LDL oxidation in part by removal of seeding LOOH species (21,22,24,26,27,32,34,51). Central to HDL-mediated antioxidative activity is the direct reduction of LOOHs by methionine residues of apoAI and apoAII, with conversion to residuespecific methionine sulfoxides (apoAI + 16, apoAI + 32, and apoAII + 16) (21,(30)(31)(32).…”
Section: Discussionmentioning
confidence: 90%
“…Equally, however, evidence is emerging that HDL-associated plasmalogens, PLs containing a vinylether bond of high oxidative susceptibility, are implicated in this potentially antiatherogenic process (26,(33)(34)(35). Indeed, it is of immediate relevance that the oxidative products of plasmalogens do not propagate lipid peroxidation, thereby attenuating formation of proatherogenic secondary oxidation products such as aldehydes (33,35,36).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16 Since then, a broad spectrum of dysfunctions of HDL in patients with cardiovascular diseases has been described, including a reduced cholesterol efflux capacity from macrophages and other cells, impaired anti-oxidative effects, a reduced ability to inhibit adhesion molecule expression on endothelial cells, a lack of the normal ability to stimulate endothelial nitric oxide bioavailability as well as diminished activities to promote endothelial cell survival. 5,39 There are several examples of dysfunction where HDL was not only characterized by loss or reduction of normal functionality but by the gain of atypical functions. For example, HDL of patients with CAD or chronic kidney disease (CKD) was found to inhibit rather than stimulate nitric oxide production because it gained the ability to interact with the lectin-like oxidized LDL receptor LOX-1 and the toll-like receptors TLR2 and TLR4, respectively.…”
Section: Dysfunctional Hdl In Cardiovascular Diseasementioning
confidence: 99%
“…Recent investigations suggest that HDL-C may lose its antiatherosclerotic properties and turn dysfunctional in patients with chronic inflammatory disorder. 31 Therefore, dysfunctional HDL-C may be another therapeutic target to reduce residual risk. 32 The present study confirmed that insulin use at the time of baseline PCI was a significant independent predictor of nontarget lesions PCI in diabetic patients after DES implantation.…”
Section: Predictors Of Progression Of Clinical Nontarget Lesions Requmentioning
confidence: 99%